Improving Student Reading Comprehension Through Question and Answer Relationships - Hanny Kusuma (English Learning Innovation (englie), 2021)
Reading comprehension is the ability to process text, understand the purpose of the text and integrate with what the reader knows. The ability of individuals to understand texts is influenced by their abilities and ability to process information. The method that researchers use in this study is the question and answer method in reading. So the teacher asks students to read a text, then after that the teacher holds a question and answer session in accordance with the reading text. The main research goals of the study is improving students reading comprehension skills with question and answer method. The implementation is doing in the classroom. After doing research with all 10th grade students, SMA Muhammadiyah 5 Jakarta. This question and answer method can make students become more diligent in reading and understanding every reading and questions given by the teacher, and for teachers, asked to provide more material and methods that can make students become more active and effective in each reading subjects. The result of is some students understand this method. And there are also students who do not like this method, but more students are successful and like this method.